Eigen dipolar electromagnetic waves of coaxial plasma-metall waveguide structure with azimuth magnetic field - Azarenkov, N.A.; Olefir, V.P.; Sporov, A.E. (Вопросы атомной науки и техники, 2013)
This report is devoted to the investigation of the propagation peculiarities of the eigen dipolar electromagnetic waves in coaxial plasma-metal waveguide with non-uniform azimuth magnetic field. The dependence of the dispersion properties, spatial attenuation coefficient, radial wave field structure, phase and group velocities on the effective collision rate, the value of the direct current that flows along the central conductor of the waveguide structure and waveguide geometric parameters were considered. It was shown that mentioned parameters can be used to control the dispersion and attenuation properties of the studied waves. Исследованы особенности собственных дипольных электромагнитных волн, распространяющихся в коаксиальном плазменно-металлическом волноводе с неоднородным азимутальным магнитным полем. Рассмотрена зависимость дисперсионных свойств, коэффициента пространственного затухания волны, радиального распределения поля волны, фазовой и групповой скоростей от эффективной частоты столкновений электронов, от величины постоянного тока, протекающего вдоль центрального проводника, а также от геометрических параметров волновода. Исследована эффективность управления дисперсией и затуханием изучаемых волн с помощью указанных параметров. Досліджено особливості власних дипольних електромагнітних хвиль, що розповсюджуються в коаксіальном плазмово- металевому хвилеводі з неоднорідним азимутальним магнітним полем. Розглянуто залежність дисперсійних властивостей, коефіцієнта просторового загасання хвилі, радіального розподілу поля хвилі, фазової та групової швидкостей залежно від ефективної частоти зіткнень електронів, від значення сталого електричного струму, що протікає уздовж центрального провідника, та від геометричних параметрів хвилеводу. Досліджено ефективність управління дисперсією та просторовим загасанням хвиль, що вивчаються, за допомогою вказаних параметрів.